Innovations in Chemical Biology - Sener, Bilge (Springer Netherlands : Imprint: Springer, 2009)
The growing role of chemistry, combined with the contribution of chemical and pharmaceutical industries to the science of mankind, are continuously advancing. The system for training researchers in the various areas of chemistry has maintained a largely traditional and single disciplinary focus, although many investigators have broadened their selection of research techniques to encompass organized and integrated programs. As a multidisciplinary, Chemical Biology is one of the fastest expanding areas of science during this century. The interdisciplinary study of molecules in living systems at a health science campus aids the integration of the traditional disciplines of chemistry and biology. This is achieved through understanding the molecular mechanisms of biological processes, which provides the opportunity to manipulate them in a defined and predictable way. Looking forward to the next century, we will witness many more remarkable achievements within Chemistry with its application to different fields, resulting in countless benefits to human health and standards of living. This book will be an excellent addition to the fields of Chemistry and Biology, in terms of both academic depth and scientific range. The focus of this book is on the chemical and molecular aspects of Chemical Biology. The interpretation of Chemistry in Biology is to some extent broader than what is commonly referred to as Chemical Biology, as it also includes topics associated with molecular biology, biochemistry, ecology, semiochemicals, and environmental and material sciences. Chemical biologists may be especially interested in chapters concerning analytical chemistry, biochemical technology, bioinformatics, catalysis and nanotechnology, carbohydrate chemistry, bioorganic and bioinorganic chemistry. The Eurasia Conference is a key component in realising the development and advancement of chemical sciences in Asia, in cooperation with European countries, as originally initiated by Prof. Dr. Hitoshi Ohtaki. In belonging to the 9th Eurasia Conference, this book encapsulates the progress being made in the field of Chemical Biology, and is therefore a fitting tribute to Prof. H. Ohtaki's memory.